Effective mass of atom and the excitation spectrum in liquid helium-4 at T = 0 K - Rovenchak, A.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
A self-consistent approach is applied for calculations within the two-time temperature Green function formalism in the random phase approximation for superfluid 4He. The effective mass of the 4He atom is computed asm m * =1.58 . The excitation spectrum is found to be in a satisfactory agreement with experiment. The sound velocity is calculated as 230 m/s. The Bose-condensation temperature with the effective mass taken into consideration is estimated as 1.99 K.